The perceived stress scale correlates with face stimulus assessment to detect stress / Siti Nadiah Sutiman and Amer Shakir Zainol - Sutiman, Siti Nadiah; Zainol, Amer Shakir (Universiti Teknologi MARA, 2018)
Stress influences the quality of life and it correlates strongly with the increasing number of mental disorder cases. Pressure related to work, environment, and relationships between friends and family members are among the issues that are often considered to be the reason of stress. This problem if left unattended, can lead to physical or mental health complications. Various stress scales were done by researchers and have been used widely to measure stress level among different communities around the world. By investigating the correlation between the Perceived Stress Scale (PSS) with Face Stimulus Assessment (FSA), the researcher's significant concern engaged in this research, is to determine which FSA is used as an art therapy medium. As a formal rating guide, the 9 scales from the Formal Elements Art Therapy Scale (FEATS) is used as the research instrument of this study is. A pre-test was carried out on 21 participants, aged between 19 years old to 30 years old that are categorized in three groups which are students, employed adults and unemployed adults. The data is obtained from a survey on PSS and FSA, completed by the participants. The findings indicate that there are correlations between both scores. Therefore, PSS and FSA rated with FEATS is a compatible tool to measure stress. However, further research needed to be done as FSA is still a work in progress to be established as a valid and well-grounded assessment. This research will be beneficial and relevant to future researches based on psychological contents analysis.